Construction of cloning‐friendly minigenes for mammalian expression of full‐length human NF1 isoforms. Issue 2 (24th November 2018) - Cui, Yan; Morrison, Helen
Abstract: The neurofibromatosis type 1 (NF1) tumor suppressor gene is one of the most frequently mutated genes in human tumors. Research on the NF1 proteins has been partially hindered by the difficulties in cloning and propagating the full‐length coding cDNAs. We have now established a condition for propagating the natural open reading frames (ORFs) and have assembled the ORFs for human NF1 type 1 and 2 isoforms. Furthermore, we were able to eliminate the cDNA cloning toxicity by introducing a mini‐intron. These NF1 minigenes were expressed similarly to the intronless version and could be used to purify full‐length NF1 proteins. The NF1 isoforms expressed from the minigenes showed Ras‐GAP activity in vivo and in vitro, while the type 1 was more potent. Our constructs expand currently available full‐length NF1 constructs and should be valuable tools in expediting the understanding of NF1, particularly the isoform‐specific functions and regulation. Abstract : Cloning‐friendly Human NF1 mini‐genes for expression of the full‐length type 1 and 2 isoforms have been constructed and the functionality has been validated. Together with the highly efficient knockdown construct, they are the new toolkit for NF1 research.